An innovative process for dealkalization of red mud using leachate from Mn-containing waste. Issue 2 (April 2022) - Li, Zehai; Gu, Hannian; Hong, Bing; Wang, Ning; Chen, Mengjun
Abstract: Red mud (RM) is an alkaline industrial solid waste discharged from Bayer process, and its high alkalinity is considered as a serious influence on environment and application. Dealkalization is prerequisite and basis for the complete utilization of RM. Mn-containing leachate is a weakly acidic wastewater generated during the storage of manganese sulfate residue. In the current study, Mn-containing leachate was used to investigate the multistage dealkalization behavior of RM. The results showed that Mn-containing leachate effectively lowered pH levels from 11.82 to 7.61 and the leaching efficiency of Na and K reached 80% and 73%, respectively, under the conditions of five-stage leaching with reaction temperature of 95 °C, reaction time of 2.0 h, and a liquid-solid ratio of 10 mL/g. X-ray fluorescence spectrometer analysis results suggested that the content of sodium oxide was reduced from 4.97% to 0.78% while the contents of SiO2, Al2 O3 and Fe2 O3 were essentially unchanged. X-ray photoelectron spectrometer and X-ray diffraction analysis revealed that hydroxycancrinite in RM was dissolved accompanying sodium released and Mn(II) appeared in the newly-generated form of charmatite in the dealkalized RM. The final dealkalized RM product was demonstrated to be with low soluble heavy metals from its water leaching test. This research provides a sustainable reference of disposal waste with waste for the dealkalization of RM, and the findings of this work demonstrate a new mechanism of replacement Na with Mn in RM dealkalization process. Graphical Abstract: ga1 Highlights: An innovative dealkalization process on red mud of using Mn-containing leachate is proposed. Mn-containing leachate can effectively remove Na (80%) and K (73%) from red mud. The loss amounts of Si, Al and Fe from red mud are slight avoiding affecting subsequent utilization. The dealkalized red mud products have low solubility of heavy metals.